2021
DOI: 10.1007/s40820-020-00579-y
|View full text |Cite
|
Sign up to set email alerts
|

Defect and Doping Co-Engineered Non-Metal Nanocarbon ORR Electrocatalyst

Abstract: Exploring low-cost and earth-abundant oxygen reduction reaction (ORR) electrocatalyst is essential for fuel cells and metal–air batteries. Among them, non-metal nanocarbon with multiple advantages of low cost, abundance, high conductivity, good durability, and competitive activity has attracted intense interest in recent years. The enhanced ORR activities of the nanocarbons are normally thought to originate from heteroatom (e.g., N, B, P, or S) doping or various induced defects. However, in practice, carbon-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(118 citation statements)
references
References 163 publications
(360 reference statements)
2
116
0
Order By: Relevance
“…[22,89,90] Hence, like electrochemical oxidation, chemical oxidation of carbon near the M-N 4 sites also leads to demetalization along with structural disintegration of the catalytic layer. [88,89,91] In addition, some researchers have suggested that demetalization and micropores flooding may also be related to carbon oxidation; more studies are needed to figure out the detailed mechanisms. [84,[92][93][94] Therefore, advanced in situ characterizations are required to detect the interplay between different decline mechanisms, such as the in situ X-ray absorption spectroscopy (XAS) to measure the metal species and chemical bond changes after the long-term operation, in situ Raman to detect the change of carbon frameworks by analyzing the vibration and rotation energy level of the substance, and in situ Mössbauer spectroscopy for Fe-N x structure analysis through probing coordination structure changes.…”
Section: Carbon Oxidationmentioning
confidence: 99%
“…[22,89,90] Hence, like electrochemical oxidation, chemical oxidation of carbon near the M-N 4 sites also leads to demetalization along with structural disintegration of the catalytic layer. [88,89,91] In addition, some researchers have suggested that demetalization and micropores flooding may also be related to carbon oxidation; more studies are needed to figure out the detailed mechanisms. [84,[92][93][94] Therefore, advanced in situ characterizations are required to detect the interplay between different decline mechanisms, such as the in situ X-ray absorption spectroscopy (XAS) to measure the metal species and chemical bond changes after the long-term operation, in situ Raman to detect the change of carbon frameworks by analyzing the vibration and rotation energy level of the substance, and in situ Mössbauer spectroscopy for Fe-N x structure analysis through probing coordination structure changes.…”
Section: Carbon Oxidationmentioning
confidence: 99%
“…Defect sites in heteroatom-doped carbons, which include point defects, corners, edges, and heteroatom-associated sites or species, are known to govern many properties of these materials, [30b,82] including their electrocatalytic activities. [83] While creating defects at the expense of ordered basal planes in these materials can substantially increase the density of such catalytic active sites for adsorption and electrocatalysis, it can compromise the degree of conjugation, electrical conductivity, and charge transfer processes in the materials. Thus, it is necessary to form the largest density of defect-related catalytic active sites while maintaining or even increasing the conductivity of the materials.…”
Section: Charge Transfer Associated With Dopants and Defect Sitesmentioning
confidence: 99%
“…However, the major blocks hindering the widespread application of fuel cells include the high cost and vulnerability of Pt/C, as well as the sluggish ORR [5–7] at the cathode, which arouses broad attention in the exploration of catalysts with earth abundance, low‐cost and excellent performances toward ORR. At present, there are many non‐Pt‐based catalysts [8–12] that have been studied, such as transition metal‐based catalysts [13–17] and heteroatom‐doped carbon‐based catalysts [18–22] . Among them, heteroatom‐doped carbon‐based materials with obvious advantages of high conductivity, good durability and excellent activity have attracted considerable attention in recent years [23] .…”
Section: Introductionmentioning
confidence: 99%